Mechanisms of KRAS inhibitor resistance in KRAS-mutant colorectal cancer harboring Her2 amplification and aberrant KRAS localization - Kohei Maruyama; Yuki Shimizu; Yumi Nomura; Tomoko Oh-hara; Yuki Takahashi; Satoshi Nagayama; Naoya Fujita; Ryohei Katayama (npj Precision Oncology)
Abstract KRAS-specific inhibitors have shown promising antitumor effects, especially in non-small cell lung cancer, but limited efficacy in colorectal cancer (CRC) patients. Recent studies have shown that EGFR-mediated adaptive feedback mediates primary resistance to KRAS inhibitors, but the other resistance mechanisms have not been identified. In this study, we investigated intrinsic resistance mechanisms to KRAS inhibitors using patient-derived CRC cells (CRC-PDCs). We found that KRAS-mutated CRC-PDCs can be divided into at least an EGFR pathway-activated group and a PI3K/AKT pathway-activated group. In the latter group, PDCs with PIK3CA major mutation showed high sensitivity to PI3K+mTOR co-inhibition, and a PDC with Her2 amplification with PIK3CA minor mutation showed PI3K-AKT pathway dependency but lost KRAS-MAPK dependency by cytoplasmic localization of KRAS. In the PDC, Her2 knockout restored KRAS plasma membrane localization and KRAS inhibitor sensitivity. The current study provides insight into the mechanisms of primary resistance to KRAS inhibitors, including aberrant KRAS localization.